Microwave rapid hydrolysis induced two-dimensional NiFeSe nanosheets for efficient oxygen evolution reaction. (14th October 2021) - Ma, Yu; Wang, Feng-Ge; Fan, Ruo-Yao; Wang, Hui-Ying; Yu, Wen-Li; Liu, Hai-Jun; Chi, Jing-Qi; Wang, Lei; Chai, Yong-Ming; Dong, Bin
Abstract: The key to the development of renewable energy is to search a cheap and efficient non-precious metal based oxygen evolution reaction (OER) electrocatalyst. The NiFe-based catalyst showed excellent catalytic properties. Herein, nickel-iron selenide (m-NiFeSe) with a two-dimensional nanosheet structure was prepared by using the nickel foam as the substrate and the electrodeposition-microwave rapid hydrolysis method. The presence of microwave not only changes the microscopic morphology, forms a new catalytic interface, increases the active area, but also appears mixed valence states of nickel (Ni 2+ /Ni 3+ ) and high valence states of selenium, which makes the catalyst possess excellent basic OER electrocatalytic performance. In addition, the synergistic effect between nickel metal and iron metal is also one of the reasons for the improved property. Finally, the microwave-assisted catalysts reached electric current densities of 10 and 100 mA·cm −2 at overpotentials of 128 and 291 mV, separately, and had good durability in the chronopotentiometry test at a current density of 100 mA·cm −2 for 18 h. The purpose of this study is to provide a simple and feasible method for the preparation of inexpensive and high-efficiency OER electrocatalysts. Graphical abstract: Image 1 Highlights: NiFeSe was synthesized by electrodeposition-atmospheric microwave two-step method. Microwave rapid hydrolysis forms a wrinkled structure and increasing catalytic area. Microwave hydrolysis makes the metal/non-metal elements present a high valence state for OER. NiFeSe delivers 100 mA cm −2 at low overpotential of 291 mV and has good stability.